Supraclavicular Block as a Sole Anesthetic Technique in Craniopagus Twins. (1st September 2013) - Schleelein, Laura E.; Perate, Alison R.; Ganesh, Arjunan
Abstract : Abstract: This is the first report in the literature of a sole regional anesthetic for adult craniopagus twins using a supraclavicular block for an elbow incision and drainage/bursa excision procedure. It demonstrates that for these complex medical patients, a total regional anesthesia technique is preferable when possible. There are several known general anesthetic complications in these patients. Anesthetic crossover between the twins can occur and may be variable; furthermore, the incidence and severity of the crossover effects of different anesthetics vary. Positioning of the twins can be difficult with both regional and general anesthesia. However, with regional anesthesia, the twins can position themselves and report any discomfort, which could go unnoticed under general anesthesia, leading to other complications. Craniopagus twins have a high likelihood of a difficult airway due to anatomy or positioning difficulties, which is avoided by regional anesthesia. This case emphasizes the unique challenges that these patients pose and the ability of regional anesthesia to help avoid the pitfalls of general anesthesia in these patients.